2010
DOI: 10.1097/prs.0b013e3181c496e4
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Nerve Reconstruction in 176 Posttraumatic Plexopathy Patients

Abstract: Early primary axillary nerve reconstruction offers rewarding glenohumeral joint stability and an acceptable range of shoulder function. Concomitant neurotization of the suprascapular nerve yielded improved outcomes in shoulder abduction and external rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…9 Best results can be achieved in cases with a preserved proximal stump of the axillary nerve that can be reconstructed via end-to-end suturing using a short nerve graft. 30 If the proximal stumps of C5-6 roots are unavailable, in cases of the avulsion or high rupture of the C5-6 roots, neurotization techniques can be used for reconstruction of the recipient nerves.…”
mentioning
confidence: 99%
“…9 Best results can be achieved in cases with a preserved proximal stump of the axillary nerve that can be reconstructed via end-to-end suturing using a short nerve graft. 30 If the proximal stumps of C5-6 roots are unavailable, in cases of the avulsion or high rupture of the C5-6 roots, neurotization techniques can be used for reconstruction of the recipient nerves.…”
mentioning
confidence: 99%
“…12 In 2009, Terzis et al looked at axillary nerve reconstructions in posttraumatic plexopathy patients and found that people younger than 20 years obtained superior deltoid power (mean = M3.18) than those older than 20 years (mean = M2.70). 10 Poor outcomes have also been associated with older patients receiving nerve transfers. In 2012, Lee et al found that deltoid strength after triceps to axillary nerve transfer correlated negatively with the age of the patient (age range, 16-79 years).…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Despite these positive findings, the literature continues to correlate increased age with poor outcomes for brachial plexus reconstructions. 2,4,[10][11][12] We present a 74-year-old male who was presented with brachial plexus palsy after a ski accident. Triceps to axillary nerve transfer, spinal accessory to suprascapular nerve transfer, and ulnar to musculocutaneous nerve transfer were performed with excellent functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Nerve transfers are a recognized treatment option for patients with traumatic brachial plexus injuries [5]. To maximize shoulder function, notably shoulder abduction and external rotation, simultaneous reconstruction of the suprascapular and axillary nerves is often advocated [6,7].…”
Section: Introductionmentioning
confidence: 99%